(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Intensive reading is a central instructional approach in foreign language education, particularly in academic and classroom-based contexts. It involves close, detailed reading of relatively short texts with the aim of developing learners’ linguistic accuracy, comprehension skills, and analytical abilities. This article provides a comprehensive, original, and plagiarism-resistant explanation of the term intensive reading, discussing its theoretical foundations, key characteristics, pedagogical objectives, classroom applications, and illustrative examples. The discussion is framed within contemporary ESL and EFL pedagogy and is suitable for submission to international academic journals.